Data Management for an Efficacy Trial of a Vaccine in the Gambia - Lahai, G. P.; Mulholland, E. K.; Hilton, S.; Fegan, G.; Inskip, G.; Yuuni, O.; Bangali, J. E.; Greenwood, B. M. (Methods of Information in Medicine, 1997)
An individually randomised double-blind trial of PRP-T Hib conjugate vaccine was conducted in the Gambia between 1993 and 1995, in which 42,848 children were randomised into one of 10 groups, five corresponding to vaccine and five to placebo. Basic demographic data were collected on all children, and administration details of all doses of EPI vaccines were recorded. In addition, details on all doses of vaccines were recorded on each child’s home-based health card; 2,681 episodes of possible Hib disease were investigated and for each episode detailed clinical data were collected. These investigations yielded 50 cases of confirmed Hib disease, which formed the basis of the final efficacy results. In all 50 cases, the data on the children’s health card, describing the doses of study vaccine received exactly, matched the vaccination database which was filled with data returned from the clinics. The data-management procedures are described in detail in this paper.
Keywords: Haemophilus Influenzae; Randomised; Data Management; The Gambia; Data Quality